-13x-10 use the distributive property which allows you to simplify
Hope this helps
Part (A)
(1 cm)/(20 cm) = (6 cm)/(x cm)
1/20 = 6/x
1*x = 20*6
x = 120
120 cm = 120/100 = 1.2 m
<h3>Answer: 1.2 m</h3>
=========================================================
Part (B)
2.2 m = 2.2*100 = 220 cm
(1 cm)/(20 cm) = (x cm)/(220 cm)
1/20 = x/220
1*220 = 20*x
20x = 220
x = 220/20
x = 11
<h3>
Answer: 11 cm</h3>
1 yard = 3 feet
Then the to find the number of feet in a number of yards use the conversion factor, 1 = 3 feet / yard
number of feet = number of yards * 3 feet/yard
If the number of feet is f and the number of yards is y, you can write the expression in this way:
f = 3y
Answer:
There are no real solutions for the given question (6c - 5) + (-6c)
Step-by-step explanation:
Solution for (6c-5) + (-6c)
Simplifying
,
(6c + -5) + (-6c) = 0
Reordering the given terms:
(-5 + 6c) + (-6c) = 0
Remove "parenthesis" around (-5 + 6c)
-5 + 6c + (-6c) = 0
Combining like terms it becomes 6c + (-6c) = 0
-5 + 0 = 0
-5 = 0
Solving
-5 = 0
we could not find the solution for the given (6c - 5) + (-6c).
The given equation is not a valid one, the "left hand side" and "right hand side" are unequal, and therefore there is no solution.